720 Pringle Versus Selective Hepatic Vascular Exclusion in Major Hepatectomy: A Systematic Review and Meta-Analysis. (12th October 2021) - Mobarak, S; Stott, M; Tarazi, M; Varley, R; Davé, M; Baltatzis, M; Satyadas, T
Abstract: Aim: Mortality and morbidity following hepatic resection is significantly affected by major intra-operative blood loss. Multiple techniques have been developed in an attempt to minimise blood loss by occluding hepatic inflow and outflow. This systematic review and meta-analysis evaluates whether selective hepatic vascular exclusion compared to a Pringle manoeuvre in hepatic resection reduces rates of morbidity and mortality. Method: A systematic review and meta-analysis were conducted according to the PRISMA guidelines by screening EMBASE, MEDLINE/PubMed, CENTRAL, SCOPUS and bibliographic reference lists for comparative studies meeting the predetermined inclusion criteria. Intra- and post-operative outcome measures were investigated. Pooled odds ratios or mean differences with 95% confidence intervals were calculated using either fixed- or random-effects models. Results: Five studies were identified including two randomized controlled trials and three observational studies reporting a total of 2, 198 patients. Data synthesis showed significantly decreased rates of mortality, overall complications, patients requiring blood transfusion, air embolism, warm ischaemia time, liver failure and multi-organ failure when performing SHVE compared to a Pringle manoeuvre. Rates of hepatic vein rupture and post-operative haemorrhage remained the same. Performing SHVE resulted in a significantly longer operation time. Conclusions: Performing SHVE in major hepatectomy may result in reduced rates of morbidity and mortality when compared to a Pringle manoeuvre, although may prolong operating time. The results of this meta-analysis are based on a few high-quality studies where tumours were adjacent to major vessels. Further RCTs are required to validate these results and determine the best technique for hepatic vascular control in this patient cohort.